2018
DOI: 10.1161/circoutcomes.117.004437
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Ischemic Heart Disease

Abstract: Evolving knowledge of sex-specific presentations, improved recognition of conventional and novel risk factors, and expanded understanding of the sex-specific pathophysiology of ischemic heart disease have resulted in improved clinical outcomes in women. Yet, ischemic heart disease continues to be the leading cause of morbidity and mortality in women in the United States. The important publication by the Institute of Medicine titled "Women's Health Research-Progress, Pitfalls, and Promise," highlights the persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(108 citation statements)
references
References 95 publications
6
88
0
14
Order By: Relevance
“…It is also emphasized that the cause of these disparities is multifactorial and is associated with low levels of education and income. Some studies have previously demonstrated these inequities for cardiovascular disease 14 , for example, and also for some of the most prevalent risk factors among women with low levels of education 11 . Additionally, they have shown the high prevalence of obesity 12 , usually associated with low-income populations and racial inequalities 13,37 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is also emphasized that the cause of these disparities is multifactorial and is associated with low levels of education and income. Some studies have previously demonstrated these inequities for cardiovascular disease 14 , for example, and also for some of the most prevalent risk factors among women with low levels of education 11 . Additionally, they have shown the high prevalence of obesity 12 , usually associated with low-income populations and racial inequalities 13,37 .…”
Section: Discussionmentioning
confidence: 98%
“…A previous study with the Surveillance of Risk Factors and Protection for Chronic Diseases by Telephone Survey (Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico -Vigitel) found that women of reproductive age with low levels of education were more inactive, and had higher levels of smoking and hypertension 11 . Cardiovascular diseases are also treated and prevented to a lesser extent among women, especially those who are in positions of social vulnerability 14 . Moreover, due to gender inequality, sexist practices place women in unfavorable situations, which are further aggravated by economic inequality 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension and history of CVD, both already known to increase COVID-19 severity and mortality [ 17 ], display strong sex differences with males exhibiting a higher prevalence of disease compared to age-matched women, prior to menopausal years [ 18 , 19 ]. On the other hand, women experience relatively worse outcomes of ischemic heart disease compared with men [ 20 ]. In HF, the overall lifetime risk is similar between men and women, there are marked sex differences in the variations of this condition, with males being predisposed to HF with reduced ejection fraction (HFrEF) and females to HF with preserved ejection fraction (HFpEF) [ 21 ].…”
Section: Sex Differences In Preexisting Cardiovascular Disease Risk mentioning
confidence: 99%
“…Based on these limitations, our results should be interpreted with caution. Gender-specific differences in patients' characteristics might be related to atherosclerotic risk factors that are unique to women, including menopause, gestational hypertension and diabetes mellitus ( 18 ). However, data on sex hormone levels and information regarding menstruation and pregnancy were not available in this study.…”
Section: Discussionmentioning
confidence: 99%